Heat capacity measurement by modulated DSC at constant temperature - Boiler, A.; Jin, Y.; Wunderlich, B.
The mathematical equations for step-wise measurement of heat capacity (Cp)by modulated differential scanning calorimetry (MDSC)are discussed for the conditions of negligible temperature gradients within sample and reference. Using a commercial MDSC, applications are evaluated and the limits explored. This new technique permits the determination of Cp by keeping the sample continually close to equilibrium, a condition conventional DSC is unable to meet. Heat capacity is measured at 'practically isothermal condition' (often changing not more than +1 K). The method provides data with good precision. The effects of sample mass, amplitude and frequency of temperature modulation were studied and methods for optimizing the instrument are proposed. The correction for the differences in sample and reference heating rates, needed for high-precision data by standard DSC, do not apply for this method.